Pengembangan Materi Ajar Menulis Tegak Bersambung Berbasis Model Pembelajaran Problem Based Learning Untuk Siswa Sekolah Dasar - Wicaksono, Meidias Abror; Irawati, Cici (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
This research aims to develop teaching materials for writing upright based on problem-based learning model with 4-D development research model (Define, Design, Develop, Disseminate). The development process begins with the define stage to identify the problems of learning to write upright, followed by the design stage to design the initial teaching materials. At the develop stage, the teaching materials were validated by material and media content experts, and tested on 26 third grade students of SDN 01 Wates Semarang. The last stage, disseminate, was conducted to disseminate the product with posters and scientific journal articles. The results showed that validation from material content experts resulted in an average score of 91% (very feasible category), while validation from media experts resulted in an average score of 93% (very feasible category). The trial of teaching materials developed for 26 third grade students of SDN 01 Wates Semarang City and the results of the comparison between pretest and posttest were -10.515, and the T-test results showed a Sig. (2-tailed) 0.000 <0.05 with an effective category.